Comparative study of psychometric properties of three assessment tools for degenerative rotator cuff disease. (February 2019) - James-Belin, Etienne; Roy, Anne Laure; Lasbleiz, Sandra; Ostertag, Agnès; Yelnik, Alain; Orcel, Philippe; Beaudreuil, Johann
Objective: To compare psychometric properties of Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire, Shoulder Pain and Disability Index (SPADI) and Constant–Murley scale, in patients with degenerative rotator cuff disease (DRCD). Design: Longitudinal cohort. Setting: One French university hospital. Methods: The scales were applied twice at one-week interval before physiotherapy and once after physiotherapy two months later. The perceived improvement after treatment was self-assessed on a numerical scale (0–4). The test–retest reliability of the DASH, SPADI and Constant–Murley scales was assessed before treatment by the intraclass correlation coefficient (ICC). The responsiveness was assessed by the paired t -test ( P  < 0.05) and standardized mean difference (SMD). The correlation between the percentage of variation in scale scores and the self-assessed improvement score after treatment was measured by the Spearman coefficient. Results: Fifty-three patients were included. Twenty-six only were available for reliability. The test–retest reliability was very good for the DASH (ICC = 0.97), SPADI (0.95) and Constant–Murley (0.92). The scale score was improved after treatment for each scale ( P  < 0.05). The SMD was moderate for the DASH (0.56) and SPADI (0.56) scales, and small for the Constant–Murley (0.44). The correlation between the percentage of variation in scores and self-assessed improvement score after treatment was high, moderate and not significant for the SPADI (0.59, P  < 0.0001), DASH (0.42, P  < 0.01) and Constant–Murley scales, respectively. Conclusion: The test–retest reliability of the DASH, SPADI and Constant–Murley scales is very good for patients with DRCD. The highest responsiveness was achieved with the SPADI.